Chapter Resisting a Total Loss of Digital Heritage Web 2.0 - Archiving & Bridging Thesaurus for Media Art Histories - Grau, Oliver (Proceedings e report, 2018)
While Media Art has evolved into a critical field at the intersection of art, science and technology, a significant loss threatens this art form due to the rapid technological obsolescence and static documentation strategies. Addressing these challenges, the Interactive Archive and Meta-Thesaurus for Media Art Research is developed to advance the Archive of Digital Art. www.digitalartarchive.at Through an innovative strategy of 'collaborative archiving,' social Web 2.0, 3.0 features foster the engagement of the international Media Art community, and a 'bridging thesaurus' linking the extended documentation of the Archive with other databases of 'traditional' art history facilitates interdisciplinary and transhistorical comparative analyses.